Estrutura filogenética e variação de caracteres funcionais em cerrados rupestres do Brasil Central - Silva, Cibele de Cássia (2016)
In this study, we investigate the role of underling evolutionary process in current phylogenetic structure of tree and shrub assemblages from rocky savanna, which is a habitat type from Cerrado biome. Besides, we analyzed whether species that occurr in both contrasting habitats types from Cerrado biome: rocky savanna and savannas, have varying functional traits in intraspecific level in response to different environmental conditions. For this, we splitted this dissertation in two chapters. In the first chapter, we aimed to understand the role of historical and evolutionary contingencies, diversification patterns and different clades distributions in shaping the current diversity of trees and shrubs from rocky savannas. Furthermore, we also seeked understanding the role of scale and species pool in phylogenetic structure of tree and shrub assemblages from rocky savanna. In the second chapter, again using trees and shrubs as study model, we investigated the occurrence of different ecological strategies in individuals of the same species, according to the type of habitats in which they occurred. Specifically, we addressed the variation of functional traits in species occurring both in rocky savannas such as in geographically adjacent savannas.